2014
DOI: 10.1186/s12933-014-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricle free wall mechanics in metabolic syndrome without type-2 diabetes: effects of a 3-month lifestyle intervention program

Abstract: BackgroundGrowing evidence demonstrates subtle left ventricular myocardial dysfunction in patients with metabolic syndrome (MetS), with central obesity, glucose intolerance and inflammation emerging as important contributors. Whether these results can be translated to the right ventricle (RV) is not yet fully elucidated. Furthermore, although lifestyle intervention favorably impacts MetS components and inflammatory biomarkers, its effect on RV myocardial function remains unknown today.MethodsThirty-nine MetS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Insulin resistance is associated with early left ventricular changes [26,27]. There are reports that insulin resistance without overt diabetes can also affect right ventricular systolic and diastolic functions assessed by novel echocardiographic techniques [28–30].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is associated with early left ventricular changes [26,27]. There are reports that insulin resistance without overt diabetes can also affect right ventricular systolic and diastolic functions assessed by novel echocardiographic techniques [28–30].…”
Section: Discussionmentioning
confidence: 99%
“… 16) 17) 18) 19) Speckle tracking echocardiography is a highly sensitive technique used to detect subtle myocardial dysfunction of systolic abnormalities. 20) 21) 22) Many studies revealed regional analysis of RV using strain analysis in patients undergoing long term exercise. 4) 5) 6) 23) Anjak et al 23) demonstrated that tricuspid annular plane systolic excursion (TAPSE) and tricuspid annular systolic velocity are reliable and accurate measures of the RV response to exercise during a supine bicycle stress echocardiography protocol.…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of references that describe the favorable impact of healthy dieting and physical activity in patients with MS, lifestyle intervention based on dietary management and physical exercise is a well-established approach to the management of various cardiometabolic diseases, including diabetes, obesity and MS [4]. Increasing evidence reports favorable and specific effects of lifestyle interventions on central obesity, insulin-resistance, glucose intolerance and inflammation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently benign and require no treatment. However, in some cases they may be so frequent (over 15-20/minute) that they may cause the heart to beat inefficiently enough to cause symptoms which may need to be addressed [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation